Enhancing Endodontic Outcomes with the Synergistic Microbicidal and Activated Root-Cleansing Technique (SMART): A Novel Approach to Root Canal Irrigation - Max Foroughi; Sara Abolmaali; Hamid Abedi; Theodore Ravenel (Medicina)
Background and Objectives: Successful endodontic treatment requires thorough disinfection and removal of the smear layer to prevent reinfection. However, conventional irrigants like sodium hypochlorite (NaOCl) and ethylenediaminetetraacetic acid (EDTA) can compromise dentin integrity. This study assessed the efficacy of the Synergistic Microbicidal and Ablative Root canal Technique (SMART), which integrates AromaRoot, a biocompatible irrigation solution based on quaternary ammonium compounds, with 980 nm diode laser activation, to enhance bacterial reduction and smear layer removal. Materials and Methods: Sixty extracted single-rooted human teeth were inoculated with Enterococcus faecalis and divided into four treatment groups using NaOCl, AromaRoot, and 980 nm laser, either alone or in combination. Bacterial counts were measured as colony-forming units per milliliter (CFU/mL). For smear layer analysis, 56 extracted teeth were prepared and irrigated using EDTA, AromaRoot, and laser activation, followed by scanning electron microscopy to evaluate dentinal tubule exposure. Data were analyzed using Kruskal–Wallis and ANOVA. Results: The combination of AromaRoot, NaOCl, and laser activation achieved a 99.00% bacterial reduction (from 8082 to 60 CFU/mL, p < 0.001), outperforming NaOCl alone (98.34%, 131 CFU/mL). For smear layer removal, AromaRoot with laser achieved 78.5% open dentinal tubules in the apical third, significantly higher than EDTA alone (64.5%, p < 0.05), though EDTA remained superior in the coronal third (89.0% vs. 81.0%, p > 0.05). Conclusions: The SMART technique significantly improves both disinfection and smear layer removal in root canal therapy, particularly in the apical region. These findings suggest that AromaRoot, especially when laser-activated, may serve as a safe and effective alternative to conventional irrigants, warranting further clinical evaluation.